ANALISIS KONFLIK PEMANFAATAN LAHAN DI KAWASAN TAMAN NASIONAL GUNUNG HALIMUN SALAK - Windra Kurniawan; Cecep Kusmana; Sambas Basuni; Aris Munandar; Kholil Kholil (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2013)
The purpose of this research is to analyze the spatial conflict between Gunung Halimun Salak National Park (TNGHS) area and the regency area around the national park. The spatial approach was used to analyse potential of spatial conflict in that region.The management TNGHS still face constraints related to the extent of forest area that could potentially conflict with the spatial three counties around TNGHS, namely Lebak, Bogor, and Sukabumi Districts. The absence of an agreement between the Ministry of Forestry and the local governments to synchronize the National Park boundary into the District Spatial Planning is still a big problem facing by the Management of the TNGHS.Therefore, conservation-based community development model must be designed properly.Keywords: Landuse conflicts, spatial analysis, suitability of the pattern space